2015
DOI: 10.4102/aej.v3i1.109
|View full text |Cite
|
Sign up to set email alerts
|

Development of South Africa’s national evaluation policy and system 2011−2014

Abstract: There is a growing recognition of the complex relationship between evaluation and research, and policy and practice. Policy making is inherently political, and public administration is contingent on various factors, that is budgets, capabilities and systems other than evidence. This has evolved in the Department of Planning, Monitoring and Evaluations (DPME) in South Africa challenging conventional ideas of communication between evaluators and policymakers and practitioners. These are characterised by monologu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…This is supported by Sherriff et al (2019) who also found that involvement of diverse stakeholders in research processes increased appreciation of the process and the outcomes. Also, research into the South African DPME evaluation system found that involving policymakers in the evaluation process increased integration of experiences and knowledge from implementation in the interpretation of evaluation findings and produced more actionable recommendations (Amisi 2015). Creating space for collaborative management of the evidence generation process can build on existing relationships in a sector and facilitate new ones as people get to know each other over the course of the evidence journey.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is supported by Sherriff et al (2019) who also found that involvement of diverse stakeholders in research processes increased appreciation of the process and the outcomes. Also, research into the South African DPME evaluation system found that involving policymakers in the evaluation process increased integration of experiences and knowledge from implementation in the interpretation of evaluation findings and produced more actionable recommendations (Amisi 2015). Creating space for collaborative management of the evidence generation process can build on existing relationships in a sector and facilitate new ones as people get to know each other over the course of the evidence journey.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, to effectively ensure use of knowledge generated through these different tools requires an understanding of the policy environment. It is not possible for those producing evidence to have all the knowledge of the policymaking departments (Amisi 2015;Stewart et al 2019). At the same time, policy actors and implementers cannot be expected to have expertise in all evidence-generation processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation